Motor and cognitive outcome after specific early lesions of the brain – a systematic review. (March 2016) - Hielkema, Tjitske; Hadders‐Algra, Mijna
Abstract : The aim of this systematic review was to study motor and cognitive outcome in infants with severe early brain lesions and to evaluate effects of side of the lesion, sex, and social economic status on outcome. A literature search was performed using the databases Pubmed and Embase. Included studies involved infants with either cystic periventricular leukomalacia (cPVL), preterm, or term stroke (i.e. parenchymal lesion of the brain). Outcome was expressed as cerebral palsy (CP) and intellectual disability (mental retardation). Median prevalence rates of CP after cPVL, preterm, and term stroke were 86%, 71%, and 29% respectively; of intellectual disability 50%, 27%, and 33%. Most infants with cPVL developed bilateral CP, those with term stroke unilateral CP, whereas after preterm stroke bilateral and unilateral CP occurred equally often. Information on the effects of sex and social economic status on outcome after specific brain lesions was very limited. Our findings show that the risk for CP is high after cPVL, moderate after preterm stroke, and lowest after term stroke. The risk for intellectual disability after an early brain lesion is lower than that for CP. Predicting outcome at individual level remains difficult; new imaging techniques may improve predicting developmental trajectories. What this paper adds: Severe brain lesions in preterm infants are associated with a high risk for cerebral palsy (median prevalence >70%); the risk is highest in infants with cystic periventricular leukomalacia (median prevalence 86%) About 30% of infants with term stroke is diagnosed with cerebral palsy. An early lesion of the brain is in 27‐50% (median prevalence) of infants associated with intellectual disability.